ANALISIS DAN STRATEGI PEMASARAN KOMODITAS CENGKEH (Syzigium aromaticum) - Vhyda Hamidah Aulia Radjaloa; Rahman Mappangaja; Ida Rosada (Percetakan Umi Toaha Makassar, 2021)
The objectives of this study were (a) To get a clear picture of the marketing strategy for clove commodities in Kalaodi Village, Tidore City, North Maluku, (b) To analyze the level of profitability of the clove commodity on farmers' income in Kalaodi Village, Tidore City, North Maluku and analyzing the margin and distribution of clove commodity marketing margin in Kalaodi Village, Tidore City, North Maluku.This research was conducted in Kalaodi Village, Tidore City, North Maluku Islands. This research lasted for about two months, from February to March 2020. Primary data collection using questionnaires to 33 respondents, data analysis using SWOT analysis and profitability analysis.The results showed that the marketing margin and distribution of clove farming marketing margins in Kalaodi Village, Tidore Islands City, North Maluku can be explained that the total marketing margin of collectors is Rp. 5,000 / Kg, while the inter-island merchant marketing margin is Rp. 10,000 / Kg.The cumulative value of the average weakness factor is only 2.99, this situation indicates that the strength factor for the clove commodity development strategy is greater than the weakness factor that will hinder the marketing of the clove commodity.Therefore, assistance from the government is very much needed in the form of technology assistance and promotion of the clove commodity marketing system in Kalaodi Village, Tidore Islands City, North Maluku.